ALIH KODE BAHASA INGGRIS DALAM LIRIK LAGU JEPANG ONE OK ROCK - SULENGKENDAGE, JAN P.; LASUT, THERESIA M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABCTRACT This research has a title: Alih Kode Dalam Lirik Lagu Jepang One Ok Rock. The  research was conducted in order to find out three types of code switching based on the Poplack’s theory, and to find the reason why the composer of One Ok Rock used code switching on lyrics with the six functions of Appel and Muysken theory.There were some steps done in collecting the data after mastering the theory and also lyrics. The collected data were taken from internet, when the data were identified and, the data were rewritten in to this paper and they were classified according to their types and function. Finally, the data were analyzed descriptively by using three types of Poplack’s theory , and for the function the writer used Apple and Muysken’s theories.In this research the writer found three types of code switching, as follow inter-sentential switching has thirty seven data, tag switching has twenty two data, and intra-sentential switching has thirteen data. The most code switching used in this research is intersentential switching. The writer also found out the function of code switching base on the theory by Apple and Muysken, those are ,(a) referensial,(b) phatic,(c) metalinguistic,  (d) the directive, (e), poetic functions, and while expresive function are not found in data.Keywords: Sociolinguistics, Code Switching, Lyrics